Undergraduate women in Computing: where did they come from, how are they and where they are going? - Freitas, Rosiane de (2017)
This work shows some data about women in Computing in Brazil and in Federal University of Amazonas in order to check if there are any improvement done recently when related to a more equal environment in the Technology area. It also directly analyses the impact of a program created in Federal University of Amazonas, to reduce gender gap in IT field and promote empowerment to women. In this study we have included data collected with an online survey of alumni, recent graduated and current student of Computing courses of our university.